1999
DOI: 10.1089/end.1999.13.699
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Shockwave Lithotripsy of Urinary Calculi: Comparative Study of Stone Depth in Kidney and Ureter Treatments

Abstract: Stone depth has a significant influence on treatment outcome after piezoelectric SWL for both renal and ureteral calculi. We recommend particular attention be given to corpulent patients presenting with ureteral stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…9,17 In the present study, results show that BC is an independent predictor for ESWL failure for MLU calculi. For patients in the supine position, the bladder and pelvic ureter may move significantly downwards, 18 thereby affecting SSD for MLU calculi.…”
Section: Discussionsupporting
confidence: 55%
“…9,17 In the present study, results show that BC is an independent predictor for ESWL failure for MLU calculi. For patients in the supine position, the bladder and pelvic ureter may move significantly downwards, 18 thereby affecting SSD for MLU calculi.…”
Section: Discussionsupporting
confidence: 55%
“…It has been suggested that the lower success rates of ESWL in morbidly obese patients observed in other studies may have been related to increased absorption of the shockwave by thicker tissues in these patients. [18,19] Furthermore, the lower success rates observed in obese patients may have also been related to the increased difficulty in localizing the stone and focusing the ESWL beam.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ESWL efficacy in obese patients is not as high as in non-overweight patients, mainly due to poorer identification of the stone, increased skin-to-stone distance and the shock-wave attenuation by body fat, which has some effect on the efficiency of stone fragmentation [7,11,17,19,21].…”
Section: Discussionmentioning
confidence: 99%